THE USE OF CONFERENCE VIDEO APPLICATION MEDIA “ZOOM” AS ALTERNATIVE MEDIA TO IMPROVE STUDENT’S SPEAKING ABILITY OF SOME STUDENTS AT SENIOR HIGH SCHOOL TWO JOMBANG - Fajar Shodik (Graduate Program, University of Islam Malang, 2021)
ABSTRACT Shodik, Fajar.2020.THE USE OF CONFERENCE VIDEO APPLICATION MEDIA “ZOOM” AS ALTERNATIVE MEDIA TO IMPROVE STUDENT’S SPEAKING ABILITY OF SOME STUDENTS AT SENIOR HIGH SCHOOL TWO JOMBANG.Thesis, English Education Department, University of Islam Malang Postgraduate Program. Advisor: Dr.Muhammad Yunus, M.Pd. Key words: speaking ability, video conference, zoom application Abstract:this research aimed to take part to do the research with the different reason and the aim. The gaps in this current research is using online conference video media, to teach the students in senior high school, in the middle of virus pandemic period, especially in Indonesia. With the target of ability is speaking ability with supported by “zoom” conference video online as media which has function to improve the eleven grade form one of Senior High School two Jombang (SMAN 2 JOMBANG). And the result will be measured by knowing the increasing speaking ability score between students who use the online video media or not. Research problem here is to know How Can Zoom conference video application as alternative media are able to improve the student’s speaking ability for eleven grade at senior high school two jombang east java. the research objective here is This study tries to improve the effectiveness of Zoom conference video application as alternative media for student’s speaking ability at senior high school two jombang east java. In this research applied Classroom action research to conduct it. By combining role play and think pare share learning method in applying during the research. And the next applying the two cycles, the researcher set up some actual ways to improve the speaking skill and the ability of eleven grade students at Senior high school two Jombang. with zoom conference video media. For the First, Actions using the